2020
DOI: 10.1103/physrevc.101.044901
|View full text |Cite
|
Sign up to set email alerts
|

Exploring non-equilibrium quark-gluon plasma effects on charm transport coefficients

Abstract: Heavy flavor particles are promising probes for the properties of the quark-gluon plasma (QGP) which is produced in relativistic heavy-ion collisions. The interaction of heavy quarks with equilibrated matter can be described by transport coefficients. In heavy-ion collisions matter is not completely thermalized. In this article we investigate how the drag coefficient A andq , the transverse momentum transfer by unit length, of charm quarks are modified if the QGP is not in complete thermal equilibrium using th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The authors find that the glasma phase can have a sizable contribution to momentum broadening and energy loss of heavy quarks. At later stages of the non-equilibrium evolution when the quasiparticle description is valid, recent studies have indicated that the pre-equilibrium effects can be important [14,15]. In [16] jet momentum broadening in the glasma was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The authors find that the glasma phase can have a sizable contribution to momentum broadening and energy loss of heavy quarks. At later stages of the non-equilibrium evolution when the quasiparticle description is valid, recent studies have indicated that the pre-equilibrium effects can be important [14,15]. In [16] jet momentum broadening in the glasma was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Such a behavior could be interpreted as preformation of modes which turn upon cooling into the corresponding quasi-particles at lower temperatures. We leave the investigation of spectral functions to separate follow-up work and focus on implications of (3) - (9).…”
Section: Probe Vector Mesonsmentioning
confidence: 99%
“…Since heavy quarks emerge essentially in early, hard processes, they witness the course of a heavy-ion collision -either as individual entities or subjects of dissociating and regenerating bound states [2,3,4]. Accordingly, the heavy-quark physics addresses such issues as charm (c,c) and bottom (b,b) dynamics related to transport coefficients [5,6,7,8,9] in the rapidly evolving and highly anisotropic ambient quark-gluon medium [10,11] as well as cc / bb states as open quantum systems [12,13,14,15]. The rich body of experimental data from LHC, and also from RHIC, enabled a tremendous refinement of our theoretical treatment which grew up on initiating ideas like "Mott mechanism and the hadronic to quark matter matter phase transition" [16], "J/ψ suppression by quark-gluon plasma formation" [17], "Dissociation kinetics and momentum dependent J/ψ suppression" [18], and "Statistical hadronization of charm in heavy ion collisions at SPS, RHIC and LHC" [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since heavy quarks essentially emerge in early, hard processes, they witness the course of heavy-ion collision-either as individual entities or subjects of dissociating and regenerating bound states [3][4][5]. Accordingly, the heavy-quark physics addresses such issues as charm (c,c) and bottom (b,b) dynamics related to transport coefficients [6][7][8][9][10] in the rapidly evolving and highly anisotropic ambient quark-gluon medium [11,12] as well as cc and bb states as open quantum systems [13][14][15][16]. The rich body of experimental data from LHC, and also from RHIC , enabled a tremendous refinement of our understanding of heavy-quark dynamics.…”
Section: Introductionmentioning
confidence: 99%